Legalizing drugs: crime stopper or social risk? - Goldstein, Margaret J. (USA today's debate:)
Introduction: crime and punishment -- A history of drug use and abuse -- The war on drugs -- A lost cause? -- A war worth fighting -- The potential of legalized drugs -- The risks of legalized drugs -- Is marijuana different? -- Voice of the people